2021
DOI: 10.1136/jitc-2021-003156
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunotherapy with nivolumab and ipilimumab in patients with rare gynecological malignancies: results of the CA209-538 clinical trial

Abstract: BackgroundPatients with rare cancers represent 55% of all gynecological malignancies and have poor survival outcomes due to limited treatment options. Combination immunotherapy with the anti-programmed cell death protein 1 (anti-PD-1) antibody nivolumab and the anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4) antibody ipilimumab has demonstrated significant clinical efficacy across a range of common malignancies, justifying evaluation of this combination in rare gynecological cancers.MethodsThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…However, TMB is not indicative of response across all cancer types [86], and "TMB high" cut-offs vary widely [87]. Moreover, as mentioned previously, some success with immunotherapy in uLMS has been observed [62,63,66].…”
Section: Genomic Landscapementioning
confidence: 94%
See 1 more Smart Citation
“…However, TMB is not indicative of response across all cancer types [86], and "TMB high" cut-offs vary widely [87]. Moreover, as mentioned previously, some success with immunotherapy in uLMS has been observed [62,63,66].…”
Section: Genomic Landscapementioning
confidence: 94%
“…Two case studies involving patients with metastatic uLMS reported dramatic reductions in tumour burden and symptomatic disease with immune checkpoint inhibitor therapy [62,63], yet clinical trials on small patient cohorts have as yet failed to show any response to anti PD-1 therapy in uLMS [64,65]. However, in a basket study of doublet immunotherapy involving nivolumab and ipilimumab for four cycles followed by maintenance nivolumab [66], two patients had complete response and a third showed a partial response out of the five uLMS patients enrolled. This observation requires further investigation.…”
Section: Treatmentmentioning
confidence: 99%
“…The Australian trial CA209-538 examined the chemotherapy-free combination regimen of ipilimumab and nivolumab and yielded an ORR of 23% (all partial responses), however with a relatively modest mPFS of 2.9 months and mOS of 5.7 months. 61 …”
Section: Palliative Therapy In Btcmentioning
confidence: 99%
“…Although OCS demonstrate a copy number high phenotype in 15/17 cases, 104 PD-L1 expression and CD8+ T-cell infiltration are a feature of this disease, 105 with whole exome sequencing of a single OCS sample demonstrating the presence of multiple tumour specific neo-antigens. 106 Within the CA209-538 study, one PR and one SD were reported in five patients with OCS who received treatment with nivolumab and ipilimumab 107 with an additional case report of a PR in recurrent OCS following treatment with pembrolizumab. 108…”
Section: Ovarian Carcinosarcomamentioning
confidence: 99%